Desarrollo de agujas hipodérmicas de bajo coeficiente de fricción para reducir la sensación de dolor - Rodríguez Lelis., J. M.; Arellano Cabrera., J. A.; Navarro Torres., J.; Reyes Galindo., S.; Abúndez Pliego., A.; Vargas Treviño., M. (Revista Mexicana de Ingenieria Biomedica, 2009)
Drugs and other substances are generally applied through hypodermic needles. Pain is felt during the insertion of the needle into the body. This pain is attributed to shear, friction, and adhesive forces generated during the insertion. The present work shows the coating process by grinding and their application on the manufacturing of low frictional hypodermic needles. Resistance test on ballistic gel showed a reduction of friction coefficient and because of it the improvement needle insertion into soft tissues thys, in consequence reducing the pain sensation.